SOCIALIZATION OF THE INFLUENCE OF DIGITAL LITERACY ON VIOLENCE ON CHILDREN - Gunadi, R. Andi Ahmad; Harmonis, Harmonis; Uswadi, Aos; Nugroho, Sidiq (LPPM Univ. Ibn Khaldun Bogor, 2023)
Violence against children that occurs repeatedly over a long period will cause serious injury to children, leave scars both physically and psychologically, and can even cause death. To reduce acts of violence against children, parents and teachers can do it in form of direct education, identification, and trial and error. Qualitative descriptive service method, respondents in grade 2 SMPI Al-Fatih, Cirendeu. Research objective: to know acts of violence in children. Research results: acts of violence that occurred in this study in the form of physical, emotional, neglect, and exploitation, are still in the low category. Conclusion: to reduce acts of violence against children, the role of parents and teachers must still be increased through various activities, for example, socialization of acts of violence against children which can be carried out on the first day of school for grade 1 students.